JunB suppresses cell proliferation by transcriptional activation of p16(INK4a) expression - Passegué, Emmanuelle (Oxford University Press, 2000)
A role for the transcription factor JunB in proliferation control was investigated in genetically modified mouse fibroblasts. Increased JunB expression induced high levels of the cyclin-dependent kinase inhibitor p16(INK4a), leading to premature senescence in primary cells and reduced proliferation in 3T3 cells, whereas lack of JunB expression results in decreased p16 levels. Furthermore, JunB-mediated p16 induction in 3T3 cells completely abolished cyclin D-associated kinase activity, resulting in reduced pRb hyperphosphorylation and G(1)-phase extension. Moreover, three AP1-like binding sites were identified in the p16 promoter through which JunB directly activates p16 transcription. Elevated JunB expression in 3T3 cells also inhibited Ras- and Src-mediated transformation and tumour growth in vivo. The suppressive effect of JunB on cell proliferation was shown to be dependent on p16 since it did not occur in INK4a(–/–) fibroblasts that lack both p16 and p19(ARF). These results demonstrate that p16 is a direct transcriptional target gene of JunB and identify JunB as a negative regulator of cell proliferation.